Successful retrieval of a dislodged leadless pacemaker from the right atrium - Yu Ando; Tetsuji Morishita; Takahiro Yajima; Yoshinobu Kojima; Hiroki Kondo; Katsumi Ueno; Norihiko Morita (European Journal of Case Reports in Internal Medicine)
Background: Leadless pacemakers have been widely adopted for their safety and efficacy in treating bradyarrhythmia. While rare, device dislodgement during implantation necessitates retrieval. Case report: We present the case of a 91-year-old man with end-stage renal failure receiving maintenance dialysis, who experienced symptomatic complete atrioventricular block. During leadless pacemaker implantation, after multiple unsuccessful attempts to secure the device in the right ventricle, the device dislodged into the right atrium during tether traction. The device initially caught on the tricuspid valve before floating into the posterior right atrium near the inferior vena cava. Using a snare technique, we successfully retrieved the device within 115 minutes of dislodgement. Post-procedure imaging showed no complications. This case highlights that unexpected migration into the right atrium may facilitate safer, simpler retrieval compared to right ventricular or pulmonary artery dislodgement. Conclusions: The right atrial location offered advantages including reduced cardiac motion influence and fewer premature contractions, enabling easier capture from the inferior vena cava using the snare. Prompt recognition and management of device dislodgement during implantation procedures is of key importance.